Functional Testing of the JivaJoy Online Product Stock Management and Ordering System Software Using Black Box Testing - Jasmine Aulia Mumtaz; Kinaya Khairunnisa Komariansyah; Helena Dewi Hapsari; Bima Julian Mahardhika; Luthfi Dika Chandra; Muhammad Rafi' Rusafni; Wicaksono, Aditya; Mindara, Gema Parasti (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
This study focuses on black-box testing of JivaJoy software, an online product stock management and ordering system. The primary goal of this research is to evaluate the functionality and performance of the system's key features, including profile management, CRUD operations for admin and customer accounts, product stock management, shopping cart, order management, and AI counseling. Black-box testing was applied to assess whether these features meet expected operational standards and user requirements without considering the internal code structure. The test results indicate that most features function as expected. However, some issues were identified related to input validation, particularly with email format, phone number length, file uploads, and product stock management. Additionally, the order management and AI counseling features showed deficiencies in error handling and input validation. Based on these findings, the study recommends improvements in input validation, product stock management, shopping cart functionality, and AI counseling systems to enhance the reliability and performance of the JivaJoy platform. These enhancements are essential to deliver more efficient, secure, and optimal services, ensuring better user experiences and customer satisfaction.